Pharmacological effects of baicalin in lung diseases - Wang, Duoning; Li, Yi (Frontiers in Pharmacology, 2023)
The flavonoids baicalin and baicalein were discovered in the root of Scutellaria baicalensis Georgi and are primarily used in traditional Chinese medicine, herbal supplements and healthcare. Recently, accumulated investigations have demonstrated the therapeutic benefits of baicalin in treating various lung diseases due to its antioxidant, anti-inflammatory, immunomodulatory, antiapoptotic, anticancer, and antiviral effects. In this review, the PubMed database and ClinicalTrials website were searched with the search string “baicalin” and “lung” for articles published between September 1970 and March 2023. We summarized the therapeutic role that baicalin plays in a variety of lung diseases, such as chronic obstructive pulmonary disease, asthma, pulmonary fibrosis, pulmonary hypertension, pulmonary infections, acute lung injury/acute respiratory distress syndrome, and lung cancer. We also discussed the underlying mechanisms of baicalin targeting in these lung diseases.